2011
DOI: 10.1111/j.1399-0012.2011.01449.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs of South African medical students toward organ transplantation

Abstract: The aim of this study was to assess and analyse the attitudes and beliefs of medical students regarding organ donation, procurement, and transplantation. Medical students at the University of Cape Town were prospectively surveyed using a self-administered questionnaire. There were 346 study participants; the mean age was 21 (range 18-33) yr, 38% were male and 62% was female. Only 8% of respondents were registered donors; clinical and white students constituted the majority of this group. Of the 315 "non-donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…The literature is replete with studies documenting dissection room experiences [76]. Many studies report on the negative emotions such as anxiety, disgust and/or apprehension experienced by students [18,19,30,35,60,78,79,88]. According to Shapiro et al [78], this anxiety is both natural and healthy, especially if it leads to reflection and self-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is replete with studies documenting dissection room experiences [76]. Many studies report on the negative emotions such as anxiety, disgust and/or apprehension experienced by students [18,19,30,35,60,78,79,88]. According to Shapiro et al [78], this anxiety is both natural and healthy, especially if it leads to reflection and self-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the results of HIV in these cases are surprisingly not disastrously bad in the setting of appropriate management and, although there may be a reporting bias at play, the relatively positive outcomes offer unique pathobiological insights into the potential interaction(s) between newly and/or previously acquired HIV infection and a suppressed immune system [229]. Building on these observations, in South Africa, where there is a high prevalence of HIV and renal failure in the setting of limited resources for healthcare, there is now an active programme of renal transplantation using HIV positive donors and recipients with short-and long-term outcomes that are acceptable for that population [230,231].…”
Section: Rna Viruses: Influenza Versus Othersmentioning
confidence: 99%
“…These worries also were raised among health students such as nursing, midwife, and medical in Turkey. 9,16,18,19,23,24,27,31 Sobnach and associates 35 found that 11% of Muslim medical students and 18% of medical students who express a belief in the afterlife are less willing to accept human or animal organs. Other points related to loss of bodily integrity are problems related to body image (which was mentioned solely by midwifery students).…”
Section: öZlem öZkan Et Al/experimental and Clinical Transplantation mentioning
confidence: 99%